Regulation of B cell function by human invariant natural killer T cells in health and autoimmune disease - Zeng, Shijuan Grace (Trinity College (Dublin, Ireland). Department of Immunology, 2011)
Invariant natural killer T (iNKT) cells are a subset of innate T lymphocytes that express a semi-invariant T cell receptor that recognises glycolipids presented on CD1d by antigen- presenting cells. They have the unique ability to stimulate both humoral and cell- mediated immune responses by direct cytotoxicity, rapid cytokine release and inducing maturation of antigen-presenting cells (APC). iNKT cells are gaining a reputation as immunoregulatory cells and have been shown to interact with B cells, the main effector of humoral immune responses. Activation of iNKT cells in mice enhances antibody responses to co-administered antigen but little is known about the phenotypic and other functional changes on B cells that occur in response to iNKT help and whether iNKT cells regulate various B cell subsets differentially, such as regulatory B cells and memory B cells. Thus the effect of co-culturing human iNKT cells on B cell maturation and antibody production in vitro was investigated, with a closer look at the effect of iNKT cells on various regulatory and memory B cell subsets. The effect of iNKT cells on B cell function was investigated in both healthy controls and SLE patients.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin